Robots at work? Pitfalls of industry level data - Karim Bekhtiar; Benjamin Bittschi; Richard Sellner (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
In a seminal paper Graetz and Michaels (2018) find that robots increase labor productivity and TFP, lower output prices and adversely aect the employment share of low-skilled labor. We show that these effects hold only, when comparing hardly-robotizing with highly-robotizing sectors and collapse, when only the latter are analyzed. Controlling for demographic workforce variables reestablishes the productivity effects, but still rejects positive wage effects and skill-biased technological change. Additionally, we find no effects, when the investigation period is extended to the most recent data (2008-2015) and document non-monotonicity in one of the instruments, which calls the respective results into question.
Keywords: E24; J24; J31; L60; O30; 330; Robots; Productivity; Technological Change